Rare bird documentation form for Peregrine Falcon at Sweet Marsh, 1978 - Schaufenbuel, Joseph P.et al (1978)
Rare bird documentation form for a Peregrine Falcon at Sweet Marsh in Bremer County, IA on April 16, 1978. Epson - sheet feed/flatbed